Market Shaping Strategies in Emerging Markets: A Critical Synthesis - Hudzaifah, Yasir; Permana, Indra Surya Permana (ICON Publisher, 2025)
This article provides a critical synthesis of the literature on market shaping strategies in emerging markets. While existing research predominantly focuses on developed economies, this review addresses the pressing need to understand how firms proactively shape markets in volatile, institutionally weak, and socio-culturally diverse environments. Drawing upon 21 rigorously selected studies, this synthesis identifies three core themes: the development of firm-level strategic capabilities, the use of cultural and institutional framing, and the innovation of business models and ecosystems. Through a thematic analysis and integrative conceptual framework, the study reveals that market shaping in emerging markets is a dynamic, multi-actor process that entails institutional entrepreneurship, ecosystem orchestration, and legitimacy-building. Unlike reactive strategies, shaping approaches in these contexts require firms to construct enabling environments, frame new norms, and often initiate the rules of the game themselves. The study contributes to the advancement of market shaping theory by offering a framework that contextualizes strategic agency within structural voids and cultural heterogeneity. Practical implications for firms, policymakers, and development actors are discussed, highlighting the importance of adaptive strategies, inclusive design, and long-term institutional engagement. The article concludes by proposing future research directions that call for longitudinal, comparative, and intersectional studies to deepen the field’s relevance across diverse emerging economies.